Mycophenolate mofetil improves lung function in connective tissue disease-associated interstitial lung disease - Fischer, Aryeh; Brown, Kevin K; Du Bois, Roland M; Frankel, Stephen K; Cosgrove, Gregory P; Fernandez-Perez, Evans R; Huie, Tristan J; Krishnamoorthy, Mahalakshmi; Meehan, Richard T; Olson, Amy L; Solomon, Joshua J; Swigris, Jeffrey J (Journal of rheumatology, 2013)
Small series suggest mycophenolate mofetil (MMF) is well tolerated and may be an effective therapy for connective tissue disease-associated interstitial lung disease (CTD-ILD). We examined the tolerability and longitudinal changes in pulmonary physiology in a large and diverse cohort of patients with CTD-ILD treated with MMF. We identified consecutive patients evaluated at our center between January 2008 and January 2011 and prescribed MMF for CTD-ILD. We assessed safety and tolerability of MMF and used longitudinal data analyses to examine changes in pulmonary physiology over time, before and after initiation of MMF. We identified 125 subjects treated with MMF for a median 897 days. MMF was discontinued in 13 subjects. MMF was associated with significant improvements in estimated percentage of predicted forced vital capacity (FVC%) from MMF initiation to 52, 104, and 156 weeks (4.9% ± 1.9%, p = 0.01; 6.1% ± 1.8%, p = 0.0008; and 7.3% ± 2.6%, p = 0.004, respectively); and in estimated percentage predicted diffusing capacity (DLCO%) from MMF initiation to 52 and 104 weeks (6.3% ± 2.8%, p = 0.02; 7.1% ± 2.8%, p = 0.01). In the subgroup without usual interstitial pneumonia (UIP)-pattern injury, MMF significantly improved FVC% and DLCO%, and in the subgroup with UIP-pattern injury, MMF was associated with stability in FVC% and DLCO%. In a large diverse cohort of CTD-ILD, MMF was well tolerated and had a low rate of discontinuation. Treatment with MMF was associated with either stable or improved pulmonary physiology over a median 2.5 years of followup. MMF appears to be a promising therapy for the spectrum of CTD-ILD.